2014
DOI: 10.5937/sanamed1402181j
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic eye infection by Ascaris lumbricoides: Case report

Abstract: 1De part ment of Oph thal mo l ogy, Cli n i cal Cen tre of Kra gu je vac in Kra gu je vac, Ser bia Ab stract: The pa r a si tic in fec tion is an af fec tion of the body as well as the eye with pa r a si tes, pro to zoa's, worms and ec to pa ra si tes, with world in ci den ce of 30%. The se di s e a ses are chro nic, sys te mic di s e a ses beca u se of we ak in na te im mu nity and abi l ity of pa r a si tes to eva de im mu ne an swer of the host or in cre a s ing the re si s tan ce to the adap ti ve im mu ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some larvae can cause complications in other parts of the body. This could lead to granulomatous peritonitis, atopic dermatitis, and eye infection [11][12][13][14][15][16][17].…”
Section: Pathology and Clinical Aspectsmentioning
confidence: 99%
“…Some larvae can cause complications in other parts of the body. This could lead to granulomatous peritonitis, atopic dermatitis, and eye infection [11][12][13][14][15][16][17].…”
Section: Pathology and Clinical Aspectsmentioning
confidence: 99%
“…Liesegang and Forster (1980) in USA reported that the yeast Candida albicans is the commonest cause of endogenous endophthalmitis, and filamentous fungi, such as Fusarium solani and Aspergillus flavus, may constitute up to one-third of all cases of traumatic infectious keratitis. Petrovic Janicijevic et al (2014) in Serbia reported that A. lumbricoides causes subconjunctival mass, granulomatous iridocyclitis, ch-oroiditis, recurrent vitreous hemorrhage, chronic dacryocystitis and invasion into a subretinal space caused by A. lumbricoides as ocular pathology. The old woman was treated by local antibiotics, corticosteroids, and Mebendazole tablets (100mg in morning for 2 weeks).…”
Section: Introductionmentioning
confidence: 99%